2016
DOI: 10.3354/meps11681
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt shifts in the Gironde fish community: an indicator of ecological changes in an estuarine ecosystem

Abstract: For decades, global climate change has directly and indirectly affected the structure and function of ecosystems. Abrupt changes in biodiversity have been observed in response to linear or sudden modifications to the environment. These abrupt shifts can cause long-term reorganizations within ecosystems, with communities exhibiting new functional responses to environmental factors. Over the last 3 decades, the Gironde estuary in southwest France has experienced 2 abrupt shifts in both the physical and chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 75 publications
(100 reference statements)
0
20
1
Order By: Relevance
“…Our study examined the evolution of phenological patterns for juveniles of several fish species and their prey in the changing climatic and hydrological environment of the Gironde estuary. Chaalali [46] and Chevillot [10] highlighted abrupt ecological shifts in the Gironde estuarine ecosystem over the last three decades. The periods between these shifts (inter-shift periods) exhibited significantly different ecological communities in terms of relative abundance, diversity and functioning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study examined the evolution of phenological patterns for juveniles of several fish species and their prey in the changing climatic and hydrological environment of the Gironde estuary. Chaalali [46] and Chevillot [10] highlighted abrupt ecological shifts in the Gironde estuarine ecosystem over the last three decades. The periods between these shifts (inter-shift periods) exhibited significantly different ecological communities in terms of relative abundance, diversity and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, many authors have reported ongoing biological effects of climate change [16] impacting species and their habitats and shaping the structure of ecological communities as well as overall functioning of ecosystems [1,710]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradations of both structure and functioning of aquatic ecosystems due to overfishing, contamination, habitat fragmentation and degradation or water extraction are now widely recognised and documented (Postel and Richter 2003;Lotze et al 2006;Worm et al 2006;Chevillot et al 2016; in this symposium: Brind'Amour et al ; Chevillot et al; Kaimuddin et al; Le Luherne et al; Olmos et al; Vogel et al). Among the drivers of global change, climate change is a major threat for ecosystems affecting all biological scales (Gattuso et al 2015): primary productivity, species distributions, and community and food web structure .…”
Section: Introductionmentioning
confidence: 99%